Internet of Things based Smart Environmental Monitoring for Mushroom Cultivation - Mohd Saiful Azimi Mahmud; Salinda Buyamin; Musa Mohd Mokji; M.S. Zainal Abidin (Institute of Advanced Engineering and Science, 2018)
Environmental condition is a significant factor that needs to be controlled in mushroom production. Mushrooms are unable to grow if the temperature is higher than 33°C or lower than 25°C. Thus, this work focuses on developing an automatic environmental control system to provide optimum condition to mushroom production house. Environmental factors considered in the system are temperature, humidity and carbon dioxide. For this, DHT11 temperature humidity sensor and MQ135 CO2 sensor are connected to the ESP8266 Wi-Fi module to become IoT (Internet of Things) sensors that send big amount of data to the internet for monitoring and assessment. This enable users to monitor the environmental condition anywhere whenever accessing the internet. Based on the analysis of the data, the system will automatically on and off the irrigation system to put the temperature at an optimum level.